Elevated threat status of large-fruited plants is associated with the extinction of large frugivores in the Caribbean islands - Fabio L. Tarazona-Tubens; Seokmin Kim; Alcides L. Morales-Pérez; Eleanor M. Hay; Maximilian G. R. Vollstädt; Thomas F. Johnson; Fernando Gonçalves; Benno I. Simmons; Christopher N. Kaiser-Bunbury; Bo Dalsgaard; Mauro Galetti; Christopher A. Searcy (Proceedings of the National Academy of Sciences, 2026)
Anthropogenic activities severely impair biodiversity and ecosystem functionality. A prime example is the loss of frugivores and their corresponding seed dispersal services due to defaunation (the decline of animal populations), ultimately affecting the continued persistence of plant species that lack their ecological partners. Loss of frugivores and their biotic interactions can be particularly severe on islands due to their isolation and relatively small area, which is often associated with low functional redundancy. From field observations on the Caribbean Virgin Islands, we found that only 1% of documented seed dispersal events occurred in large-fruited plants, with dispersal probability closely tied to overlap between fruit width and gape size of the largest nonthreatened frugivore. Using fruit–frugivore trait matching to extrapolate this pattern to the rest of the Caribbean, we found that large-fruited plant species are effectively “orphaned” due to the absence of animal dispersers, resulting in elevated rates of endangerment across islands. Threat status of plant species was better explained by trait matching than other pressures such as human use, suggesting that extinction or reduced abundance of large-bodied frugivores is compromising their plant mutualists’ ability to persist. These results argue strongly for the need to restore populations of large-bodied frugivores across the Caribbean, either through population enhancement of currently endangered species or rewilding with close relatives of extinct species.